Impact of coronavirus disease 2019 on medical practice in endocrine and metabolic diseases in Japan: a nationwide surveillance study conducted by the Japan Endocrine Society - Katsunori Manaka; Sayaka Kato; Ryuichi Sakamoto; Hajime Yamakage; Tsugumi Uema; Shiori Kawai; Megumi Shibata; Izumi Hiratsuka; Sawako Nakachi; Takeshi Onoue; Takefumi Tsuchiya; Michiaki Fukui; et al. (Endocrine Journal)
We investigated the impact of the Coronavirus disease 2019 (COVID-19) pandemic on the management of endocrine and metabolic disorders in Japan. We conducted a cross-sectional nationwide questionnaire survey targeting board-certified endocrinologists under the auspices of the Japan Endocrine Society. The questionnaire consisted of multiple-choice questions and open-ended responses. Out of approximately 2,700 specialists, 528 (19.5%) opted to participate, suggesting a high level of interest in COVID-19 management among endocrinologists. The study found that almost half of participants had encountered cases of endocrine and metabolic disorders following COVID-19 infection or vaccination. Conditions related to thyroid diseases, glucose metabolism disorders/diabetes, and hypothalamic-pituitary disorders were particularly prevalent. Diabetes and obesity were identified as having high rates of severe cases or fatalities due to COVID-19. The study also highlighted challenges in routine diagnosis and treatment, emphasizing the potential benefits of combining remote consultations with in-person visits to optimize the frequency of examinations and check-ups during infectious disease outbreak which disrupts access to healthcare providers. The insights obtained from this survey are expected to contribute to ensuring appropriate healthcare provision for patients with endocrine and metabolic disorders by using flexible consultation formats, particularly even in the conditions where medical access may be limited due to future outbreaks of emerging or re-emerging infectious diseases.